Tumor Lysis Syndrome: New Challenges and Recent Advances - Wilson, F. Perry (2014)
Tumor lysis syndrome (TLS) is an oncologic emergency triggered by the rapid release of intracellular material from lysing malignant cells. Most common in rapidly growing hematologic malignancies, TLS has been reported in virtually every cancer type. Central to its pathogenesis is the rapid accumulation of uric acid derived from the breakdown of nucleic acids, which leads to kidney failure by various mechanisms. Kidney failure then limits the clearance of potassium, phosphorus, and uric acid leading to hyperkalemia, hyperphosphatemia, and secondary hypocalcemia, which can be fatal. Prevention of TLS may be more effective than treatment, and identification of at-risk individuals in whom to target preventative efforts remains a key research area. Herein, we discuss the pathophysiology, epidemiology, and treatment of TLS with an emphasis on the kidney manifestations of the disease.